Quantified Observations of Sensory Processing (QOSP): Resource Tool for Screening Sensory Processing Difficulties in Preschoolers - Kadkol, Moushami S. (Journal of Intellectual Disability - Diagnosis and Treatment, 2014)
Sensory Processing (SP) difficulties in children are seen to be increasing in today’s world. Quite a few typically developing children are reported to have difficulties in coping with school, home and play environments. Their difficulties are mostly labeled abnormal behaviors and with superficial assessments these children often receive traditional treatments that marginally decrease their problems without giving long term functional gains. Hence their SP dysfunctions make them adopt pathological behaviors as they grow, making them incompetent as compared to their peers. One of the factors behind these children getting unnoticed at an early age is lack of awareness about SP difficulties among the parents, teachers and medical fraternity in India. The other important factors include unavailability of contributory study in this area done on the Indian population and the use of non-normated, generalized evaluation tools done for evaluation of these difficulties. Further less information on what is age related typical SP makes it trickier to differentiate between a typical behavior and SP difficulty. The present study is the first study that would make an effort to understand the age related SP in Indian preschoolers aged 3-7 years. The QOSP includes observations based on literature and theoretical constructs of SP which are graded and made quantitative for ease of administration and interpretation. This study intends to establish the age appropriate expected response and estimate the children posing risk to develop SP dysfunctions. The study further attempts to understand correlations between the different parameters of QOSP and tries to identify those parameters that can be considered red flags for SP difficulties. The results of the study suggest about 3% of children in the typically developing group to be at the risk of having SP difficulties. About 20% are estimated to be having difficulties in at least one of the SP areas when compared with behaviors rated on Sensory Processing Measure. Apart from typically developing children the tool was also used in co-morbid conditions and was found to be useful in understanding the underlying Sensory Processing difficulties. Thus the QOSP can be considered a good measure not only in screening children with suspected sensory processing difficulties but also to gear the intervention program to be streamlined and goal oriented.